Increased Water Recovery Through the Application of the TTD/Robinsky Method in Chilean Tailings Disposal Operations - Valdebenito, R; Valdivia, R (Paste 2009: Twelfth International Seminar on Paste and Thickened Tailings, 2009)
The results of Chilean copper tailings characterisation under the TTD/Robinsky methodology are presented. These results are drawn onto five cases in order to obtain a hydraulic balance of the deposits; and they are compared to a typical case of a conventional tailings dam. From the point of view of the increase of water recovery, this paper concludes that characterisation studies carried out under the thickened tailings disposal (TTD) methodology make it possible to evaluate — at a pre-feasibility level — the convenience of discharging tailings with this method.